2020
DOI: 10.1590/fst.00319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on the functional and structural properties of hydrolysates of different bovine collagens

Abstract: The ultrasound effect on functional and structural properties of hydrolysates of different bovine collagens (fibers, gelatines and hydrolysates) was evaluated. The enzymatically hydrolyzed samples (enzyme Alcalase ) with previous or simultaneous ultrasound treatment presented higher number of bands with shorter wavelengths (mid-FTOR). The ultrasound provided the samples with a higher hydrolysis degree and favored the antimicrobial activity, evidencing the advantages of its use in the process. Results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…It is clear from the figure that TPC values increased as the extraction time, temperature and ultrasound power increased for all solvent applications except PG. The increase in TPC yield as power increases can be explained by the cavitations effect caused by ultrasonic disrupting the material and allowing the formation of a porous structure (Vidal et al, 2020). Phenolics compounds due to cavitations are easily released from the plant matrix (Dranca & Oroian, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the figure that TPC values increased as the extraction time, temperature and ultrasound power increased for all solvent applications except PG. The increase in TPC yield as power increases can be explained by the cavitations effect caused by ultrasonic disrupting the material and allowing the formation of a porous structure (Vidal et al, 2020). Phenolics compounds due to cavitations are easily released from the plant matrix (Dranca & Oroian, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Vidal et al [ 34 ] observed no effect of ultrasound (use of prior or concomitant ultrasound treatment) on the degree of hydrolysis of porcine and bovine collagen under the influence of pepsin (4% enzyme addition). On the other hand, it was shown that the simultaneous action of ultrasound and 8% enzyme concentration (Alcalase 2.4 L) proved to be the most effective in the bovine collagen sample hydrolysis process, providing the best degree of hydrolysis and antioxidant activity results [ 35 ]. However, Leong et al [ 36 ] reported that ultrasound treatment breaks down aggregates of casein and whey proteins, resulting in an increased availability of these proteins for proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid hydrolysis rate of collagen tends to increase the number of collagen molecules produced that will be converted and will eventually increase the yield value (Muyonga et al, 2003). The protein content of collagens is affected by the extraction method since the more drastic extraction processes can result in lower protein contents, as they severely affect the protein structure, breaking it into smaller fractions (Vidal et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%